ROLE OF CHOLEDOCHODUODENOSTOMY REVISITED IN THE ERA OF MINIMAL INVASIVE PROCEDURES - Asad, Shawana; Haj, Zainab; Qureshi, Zaheer; Gul, Bilawal; Ahmed, Sajjad; Khattak, Irfan ud-din (Journal of Ayub Medical College Abbottabad, 2018)
Background: Present era of endoscopic and laparoscopic approaches have revolutionized surgical management of Common Bile Duct (CBD) stones. Open procedures like Choledochoduodenostomy (CDD) have become a rarity but are not completely obsolete. It may be considered a relatively safe alternative when dealing with recurrent, too large or impacted stones, a failed ERCP, and CBD stricture with stones. The aim of this study was to establish safety, efficiency, cost effectiveness and easy availability of CDD in selected patients. Methods: In this observational study, the outcome of 90 consecutive patients undergoing CDD between 1st January 1995 and 31st Dec, 2016 in surgical unit C, Ayub Medical Complex, Abbottabad was reviewed. Choledochoduodenostomy was offered to patients who refused or had a failed ERCP and when CBD size was more than 1cm. CBD was anastomosed to Duodenum using standard technique. Results: Medical records of 90 patients (age range 34-96 years) were reviewed; 5 were excluded and 85 were included in the study. Complication rate was 31.76% (n=27) including respiratory complications in 16.47% (n=14), wound infection in 10.6% (n=9), anastomotic leak in 2.35% (n=2) and Cholangitis in 1.18% (n=1) and Mortality in 1.18% (n=1). There was no evidence of Sump Syndrome. Total cost of procedure was Rs.50 as admission fee, which included daily provision of food and there were no room charges. Conclusion: Choledochoduodenostomy is a safe procedure, with fewer complications and significantly low cost. In case of ERCP failure, CDD is recommended. Keywords: Choledochoduodenostomy; failed ERCP; Open Surgery; safe; Sump Syndrome; Reflux Cholangitis